Silent struggles: Assessing physical and psychosocial burdens among caregivers of children with sickle cell disease in western Sudan–A cross-sectional study - Weaam Abdallah; Wisal Abbas; Swsan A. M. Elsharif; Maaza Hamid Ahmed Ibrahim; Walaa Abdalla; Fadwa Saad (PLoS ONE, 2025)
Sickle cell disease (SCD) is a major cause of morbidity and mortality. It poses a major health problem in Sudan, especially in the western region, where the prevalence of the disease is highest. SCD places a substantial psychosocial and economic burden on the caregivers. Given that there is no readily available effective treatment, caregiving for children with SCD is highly demanding and is associated with inescapable stress. This observational, cross-sectional facility-based study aimed to assess the caregivers’ physical and psychosocial burdens. A total of 123 caregivers who attended the Sudan Sickle Cell Anaemia Centre, El Obeid, western Sudan, were interviewed using the abridged Arabic Zarit Burden Interview Scale (ZBI-A) between March 15 and April 12, 2023. Data was then analysed using SPSS v.20 and summarised into medians and interquartile ranges. A p-value of <0.05 was considered statistically significant. The Mann-Whitney U test and Kruskal-Wallis tests were used to identify the characteristics of caregivers and their SCD children that were associated with the total Zarit burden score of the caregivers. (84.6%) of caregivers were biological mothers, (41.5%) were (20–30) years old, and (39.0%) were from outside Elobeid. Most mothers (37.4%) and fathers (39.8%) only completed primary schooling; thus, most mothers (84.6%) were housewives, and most fathers (77.2%) were free workers. (82.9%) had a family monthly income level of <100,000 SDG (<167 USD). (46.8%), (35.5%), and (17.7%) experienced mild, moderate, and severe levels of caregiving burden, respectively. Total Zarit burden scores of the caregivers were significantly associated with residing outside Elobeid (p = 0.028), lower maternal and paternal educational levels (p = 0.008) (p = 0.036), respectively, lower paternal employment status (p = 0.034) and those whose children with SCD were aged 5–9 years (p = 0.008). In conclusion, (46.8%), (35.5%) and (17.7%) of the participants experienced mild, moderate, and severe levels of caregiving burden, respectively.